Amphibian diversity of Mato Grosso do Sul State, Brazil - Souza, Franco L.; Prado, Cynthia P. A. [UNESP]; Sugai, Jose L. M. M.; Ferreira, Vanda L.; Aoki, Camila; Landgref-Filho, Paulo; Struessmann, Christine; Avila, Robson W.; Rodrigues, Domingos J.; Albuquerque, Nelson R.; Terra, Juliana; Uetanabaro, Masao; et al. (Fundacao Zoobotanica Rio Grande Sul, Museu Ciencias Naturais, 2017)
Amphibian species from Mato Grosso do Sul state were compiled and checked for the first time. A total of 97 species were recorded, representing more than 10% of the known Brazilian amphibians. Twenty five anuran genera in nine families and only one caecilian were recorded. Cerrado was the richest area followed by semideciduous forests, Chaco, and veredas ( palm swamps). It was recorded 56 species in floodplain areas and 92 in the surrounding cerrados. The Serra da Bodoquena National Park and some Pantanal areas were better sampled than other regions in Mato Grosso do Sul, resulting in sampling gaps across the state. Important areas for future inventories were identified: mountainous regions in Serra de Maracaju and those bordering the Apariver, Brazilian chacoan areas, the Taquari river alluvial fan, the broad Taquari-Itiquira flat area, the Central Plateau scarps, wet areas from Parana river bordering Sao Paulo state, and inland areas from Pantanal.
Keywords: Amphibia; inventories; biodiversity; Biota-MS Program